If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -7)(x + -8) = (x + 40)(1 + -2x) Reorder the terms: (-7 + 6x)(x + -8) = (x + 40)(1 + -2x) Reorder the terms: (-7 + 6x)(-8 + x) = (x + 40)(1 + -2x) Multiply (-7 + 6x) * (-8 + x) (-7(-8 + x) + 6x * (-8 + x)) = (x + 40)(1 + -2x) ((-8 * -7 + x * -7) + 6x * (-8 + x)) = (x + 40)(1 + -2x) ((56 + -7x) + 6x * (-8 + x)) = (x + 40)(1 + -2x) (56 + -7x + (-8 * 6x + x * 6x)) = (x + 40)(1 + -2x) (56 + -7x + (-48x + 6x2)) = (x + 40)(1 + -2x) Combine like terms: -7x + -48x = -55x (56 + -55x + 6x2) = (x + 40)(1 + -2x) Reorder the terms: 56 + -55x + 6x2 = (40 + x)(1 + -2x) Multiply (40 + x) * (1 + -2x) 56 + -55x + 6x2 = (40(1 + -2x) + x(1 + -2x)) 56 + -55x + 6x2 = ((1 * 40 + -2x * 40) + x(1 + -2x)) 56 + -55x + 6x2 = ((40 + -80x) + x(1 + -2x)) 56 + -55x + 6x2 = (40 + -80x + (1 * x + -2x * x)) 56 + -55x + 6x2 = (40 + -80x + (1x + -2x2)) Combine like terms: -80x + 1x = -79x 56 + -55x + 6x2 = (40 + -79x + -2x2) Solving 56 + -55x + 6x2 = 40 + -79x + -2x2 Solving for variable 'x'. Reorder the terms: 56 + -40 + -55x + 79x + 6x2 + 2x2 = 40 + -79x + -2x2 + -40 + 79x + 2x2 Combine like terms: 56 + -40 = 16 16 + -55x + 79x + 6x2 + 2x2 = 40 + -79x + -2x2 + -40 + 79x + 2x2 Combine like terms: -55x + 79x = 24x 16 + 24x + 6x2 + 2x2 = 40 + -79x + -2x2 + -40 + 79x + 2x2 Combine like terms: 6x2 + 2x2 = 8x2 16 + 24x + 8x2 = 40 + -79x + -2x2 + -40 + 79x + 2x2 Reorder the terms: 16 + 24x + 8x2 = 40 + -40 + -79x + 79x + -2x2 + 2x2 Combine like terms: 40 + -40 = 0 16 + 24x + 8x2 = 0 + -79x + 79x + -2x2 + 2x2 16 + 24x + 8x2 = -79x + 79x + -2x2 + 2x2 Combine like terms: -79x + 79x = 0 16 + 24x + 8x2 = 0 + -2x2 + 2x2 16 + 24x + 8x2 = -2x2 + 2x2 Combine like terms: -2x2 + 2x2 = 0 16 + 24x + 8x2 = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(2 + 3x + x2) = 0 Factor a trinomial. 8((2 + x)(1 + x)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-2, -1}
| 4v^2-49t^2=0 | | 2x+3x+4x-5=2+3+4x | | (5x+6)(x+6)=(x+10)(4x+3) | | n-10=0.5n-7 | | 36r^2+60rg+25g^2=0 | | -3=6-q/9 | | 4(3x+4)=4x+8 | | n-10=0.5-7 | | 17x=0.005 | | 3x-7=5-6x | | 25m^2-30m+9=0 | | (x-1)(x-2)=(x-5)(x+1) | | 6-2x=5x+10 | | 8-2x=3x+8 | | g(3)=1.67 | | 6x+7y=49 | | 9x-9=9(x+9) | | 17x=1.9 | | 576=10x-0.04x^2 | | -3x-9=3x-3 | | y=x^2+6x+18 | | -25=5(3q-2) | | 3.6x=2.1x+10.5 | | 8-h=12 | | 8-5= | | 0.95y+1=y-0.5 | | 3x-15=59 | | 4x+8=10x-10 | | 4-8d=16 | | 5x^4+13x^2-6=0 | | 0.7-4.2=3.6+x | | 56=-2(21-x)+4(x-4) |